Entrepreneurial orientation and sustainable business: Examining the mediating role of market orientation and financial performance in village-owned enterprises - Satria, Gde Agung; Wiagustini, Ni Luh Putu; Rahyuda, Henny; andraningrat, Ica Rika C (Edelweiss Applied Science and Technology, 2025)
Village-Owned Enterprises (VOEs) play a crucial role in enhancing the well-being of rural communities. Achieving sustainable performance requires the implementation of a business sustainability framework encompassing environmental, economic, and social dimensions. VOEs with a strong entrepreneurial orientation, market orientation, and sound financial performance are expected to achieve business sustainability. This study aims to examine and explain the influence of entrepreneurial orientation, market orientation, and financial performance on business sustainability, both directly and indirectly. A quantitative method is employed, with a sample of 113 VOEs selected for analysis. Data analysis is conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The findings indicate that entrepreneurial orientation, market orientation, and financial performance significantly influence business sustainability. Additionally, market orientation and financial performance act as mediating variables in the relationship between entrepreneurial orientation and business sustainability.